The Role of Artificial Intelligence in Pregnancy Monitoring and Complication Prevention: (Subject Review) - Faeza Fakhradeen Basas; Marwah Ali Khalaf (Journal of Science in Medicine and Life, 2025)
Artificial intelligence (AI) is a revolutionary frontier of modern obstetrics and gynecology, allowing for more advanced pregnancy monitoring, earlier diagnosis of disease processes, and improved mother–baby outcomes. AI-related technologies such as machine learning, deep learning, predictive analytics and natural language processing can analyze large-complex data sets to provide personalized risk assessment and clinical advisements. In this article, we review the state of current utilization of AI in pregnancy monitoring and discuss its clinical impact. Technical and ethical challenges are underlined. Finally, we propose future prospective direction on research and how to employ it in obstetric practice. There are indications that AI may decrease maternal and neonatal morbidity, aid in earlier interventions and improve the quality of care overall.